Territory, state and nation the geopolitics of Rudolf Kjellén - Björk, Ragnar 1948-; Lundén, Thomas 1943- (Berghahn Books, 2021)
"Rudolf Kjellén, regularly referred to as "the father of geopolitics," developed in the first decade of the twentieth century an analytical model for calculating the capabilities of great-power states and promoting their interests in the international arena. It was an ambitious intellectual project that sought to bring politics into the sphere of social science. Bringing together experts on Kjellén from across the disciplines, Territory, State and Nation explores the century-long international impact, analytical model, and historical theories of a figure immensely influential in his time who is curiously little-known today"--
Keywords: Kjellén, Rudolf -- 1864-1922; Geopolitik; Kjellén, Rudolf / 1864-1922 / Influence; Geopolitics / History; Political scientists / Sweden; Kjellén, Rudolf / 1864-1922; Geopolitics; Influence (Literary, artistic, etc.); Political scientists; Sweden; History